2023
DOI: 10.1073/pnas.2204134120
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye disease in mice activates adaptive corneal epithelial regeneration distinct from constitutive renewal in homeostasis

Abstract: Many epithelial compartments undergo constitutive renewal in homeostasis but activate unique regenerative responses following injury. The clear corneal epithelium is crucial for vision and is renewed from limbal stem cells (LSCs). Using single-cell RNA sequencing, we profiled the mouse corneal epithelium in homeostasis, aging, diabetes, and dry eye disease (DED), where tear deficiency predisposes the cornea to recurrent injury. In homeostasis, we capture the transcriptional states that accomplish continuous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Interestingly, we also found a significant causal relationship with AMD in our immunome MR analysis. Another clinical study found a significant association between CD16+ monocytes and refractory wet AMD (Lin et al, 2024). Coupled with scRNA-seq results, we hypothesize that the androgen -IL10RA -CD16+monocytes pathway is likely to be a critical immunometabolic pathway in wet AMD.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Interestingly, we also found a significant causal relationship with AMD in our immunome MR analysis. Another clinical study found a significant association between CD16+ monocytes and refractory wet AMD (Lin et al, 2024). Coupled with scRNA-seq results, we hypothesize that the androgen -IL10RA -CD16+monocytes pathway is likely to be a critical immunometabolic pathway in wet AMD.…”
Section: Discussionsupporting
confidence: 70%
“…Our prior analysis unveiled distinctive immunometabolic factors across various stages and types of AMD, prompting a systematic investigation into immune-related changes. We delved into the peripheral immune milieu at single-cell resolution in 43 AMD patients, encompassing 8 with early AMD, 6 with GA, 16 with CNV, 13 with mixed GA and CNV, alongside 22 healthy controls (Lin et al, 2024). Predominant cell populations were delineated utilizing scRNA-seq data (Figure 3A, S5A).…”
Section: Systematic Immunoprofiling Reveals Cellular and Transcriptio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal clustering of cells was performed using the assistance of the clustree R package [47]. Cell type assignment was performed using marker genes defined in murine single cell literature [48][49][50][51]. Volcano plots were created using the R package EnhancedVolcano using differentially expressed gene lists generated by Seurat's FindMarker function (Wilcoxon Rank Sum tests with P < 0.05) [52].…”
Section: Single Cell Rna Sequencing and Analysismentioning
confidence: 99%
“…Because of the convenience of obtaining materials, the richness of sources, and the low immunogenicity,3 stem cells have been applied in various fields, such as tissue engineering and regenerative medicine, in recent years 4,5. It has also contributed to the alternative treatment of some ocular diseases 4–9. Many ocular diseases, such as corneal degeneration, retinitis pigmentosa, and diabetic retinopathy, require cell tissue transplantation or vascular reconstruction.…”
mentioning
confidence: 99%